Study of Potential Antiobesity Compounds from Amylchlorogenate Derivates on Leptin Hormone and their Toxicity using Molecular Docking Approach - Faridah Faridah; Shirly Kumala; Gumilar Adhi Nugroho; Partomuan Simanjuntak (Journal of Natural Product for Degenerative Diseases, 2024)
Chlorogenic acid, a type of phenolic acid, is a polar compound that has anti-obesity effects with unclear mechanisms. This study aims to obtain compounds that are active as antiobesity, their interaction with receptors and its toxicity. This research was carried out in several steps, internal validation of targets and methods using Yasara, docking of test compounds and positive control using PLANTs, interaction visualization using Pymol and toxicity testing using Protox-II. Validation results show four receptors and test method meet the requirements. Docking results of setmelanotide on receptor code 1PXH -113.81; 2QBP -109.163; 2QBR -110.113, 2; QBS -110.817 kcal/mol respectively. The docking results of the test compounds in 1PXH namely 7,4,5-Triamylchlorogenate (compound a) -114,333 kcal/mol. In 2QBP namely 7,3'-Diamylchlorogenate (110,152) (compound b), (compound a) (-109,818), 7,4,3',4'-Tetraamylchlorogenate (compound c) (-115,309), 7,5,3',4'-Tetraamylchlorogenate (compound d) (-112,85), 7,4,5,3',4'-Pentaamylchlorogenate (compound e) (-110,414) and 2',5'-Diamylchlorogenic acid (compound f) (-113, 565) kcal/mol. In 2QBR namely, (compound a) (-114,276), (compound e) (-111,059), and (compound f) (-110,398) kcal/mol. In 2QBS namely, (compound a) (-113.53), and (compound d) (-111,676) kcal / mol. The active site of amino acids that have affinity are, ARG45 and LYS120 in 1PXH; ASP48, SER118 and ARG47 in 2QBP; ASP48 and ARG24 in 2QBR; ASP48 and GLN262 in 2QBS code. Toxicity tests obtained oral LD50 of 5000 mg/kg BW (compounds a and f); 3800 mg/kg BW (compounds b, c, d and e). The potential compound that was active in all the test receptor codes was 7,4,5-Tripentylchlorogenate (compound a). All active test compounds were relatively safe.